AKUNTABILITAS PEMERINTAHAN DESA; Sebuah Telaah atas Perdes Nomor 01 Tahun 2011 tentang Biaya Administrasi Pelayanan di Desa Landungsari Kecamatan Dau Kabupaten Malang - Khoiron, Khoiron (Universitas Merdeka Malang, 2016)
Government bureaucracy is the most visible institutions to be monitored by the societies obviously at the village level, associated with the service. As a public institution, the village government is expected to actualize the future goals of the central government under President Joko Widodo called the concept of